110 Infarct Burden Following Multivessel PCI Vs. Infarct-Only PCI in Patients with Acute Stemi: The Glasgow Prami CMR Sub-Study. (6th June 2015) - Mangion, Kenneth; Carrick, David; Payne, Alexander R; McClure, John; Mason, Maureen; Petrie, Mark; McEntegart, Margaret; Eteiba, Hany; Oldroyd, Keith; Berry, Colin
Abstract : Background: In the Preventive Angioplasty in Myocardial Infarction trial (PRAMI; ISRCTN73028481 ), immediate multivessel PCI (MV-PCI) of non-IRA lesions in patients with acute ST elevation myocardial infarction (STEMI) and multivessel coronary disease (MVD) improved long term prognosis. We assessed infarct distribution and size in a pre-specified cardiac magnetic resonance (CMR) sub-study. Methods: In this single centre prospective sub-study, PRAMI participants were invited to undergo 1.5 Tesla CMR 1 week and 1 year after primary PCI. The CMR scans were analysed using semi-automated software by a clinician blinded to treatment group assignment and clinical outcomes. The presence and extent of infarction were assessed quantitatively with late gadolinium enhancement (LGE) imaging (Gadovist, 0.1 mmol/kg). The infarct was delineated as an area of myocardial enhancement (cm 2 ) using a signal intensity threshold of >5SDs above a remote region, and expressed as a% of total LV mass. The incidence of new LGE in non-infarct related artery territories at baseline and 1 year were assessed. Data were analysed by an independent statistician. Results: Of 465 randomised trial participants in 6 UK hospitals, 138 (30%) were enrolled in Glasgow. Of these 80 patients underwent CMR 1 week post primary PCI of whom 41 (51%) were in the multi-vessel PCI group and 39 (49%) were in the IRA-only group. At 1 year, 69 (86%) patients had a follow up CMR scan. Infarct size and distribution are described in Table 1 . Conclusion: Infarct size and distribution were similar in patients treated by MV-PCI or IRA-only PCI. MV-PCI is not associated with additional MI acutely which supports the safety of this procedure in line with the benefits observed with preventive PCI in PRAMI. Funding: Golden Jubilee National Hospital; PRAMI was funded by Barts and the London Charity.